International News Coverage and the Korean Conflict The Challenges of Reporting Practices - Moon, Miri.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
This book explores journalism practices and the dynamics of international news media in Korea, and examines the ways in which Korean journalists and foreign correspondents cover new stories about the Korean conflict. Drawing on a comparative analysis of major news coverage relating to the Korean conflict across UK, US and South Korean media, it offers an insight into the role of journalism on the Korean Peninsula, how media coverage is reported, as well as its impact on Korean society and the wider international community. It notably explores news gathering practices concerning the Korean conflict, and investigates factors that influence journalists' news production through interview with foreign correspondents including bureau chiefs from news outlets as diverse as AP, Reuters, The New York Times, the BBC, Le Figaro, and the Mainichi Shimbun. Extending its coverage to provide a rationale for the proliferation of new media both from encoders and decoders' perspectives, and drawing on lively empirical data to examine the processes of news production, the book addresses how international media impacts on the stability and security in the region under the influence of the competing superpowers - the United States and China.
Journalistic Field between New Media and Raw Culture -- The historical context of the Korean conflict -- Journalism theories in media studies -- Historical contexts of the Korean press -- News Framing and In-depth Interviews -- International news coverage of the Korean conflict -- Reporting international conflicts - Dynamics and Challenges -- Discussion and Conclusion.
Keywords: Journalism; Asia -- Politics and government; Communication; Journalism; Asian Politics; Media and Communication